Fluorescence enhancement in crystals tuned by a molecular torsion angle: a model to analyze structural impact. Issue 27 (24th June 2016) - Srujana, P.; Gera, Tarun; Radhakrishnan, T. P.
Abstract : Alkyl group substitutions induce a systematic tuning of an intramolecular torsion angle and supramolecular organization resulting in a parallel increase in the fluorescence enhancement (solution to crystal) factor. A model is developed to probe the molecular and crystal structural impact on fluorescence enhancement, and provide a basis for rational design. Abstract : Development of a coherent picture of enhanced fluorescence in the aggregated/solid state of molecular materials requires an exploration of the concomitant inhibition of intra and intermolecular non-radiative energy loss pathways. This necessitates a fluorophore that exhibits a systematic variation of the emission enhancement (solid over solution) upon subtle structural tuning at the molecular and supramolecular levels. Diaminodicyanoquinodimethanes with an imidazolidine moiety (1a ), reported in 1962 but never structurally characterized, is shown to be ideally suited for this.1a and its N -ethyl (1b ) and N, N ′-dimethyl (1c ) derivatives are synthesized by a modified route and structurally characterized. Systematic change in the molecular structure (a crucial torsion angle varying from ∼3° to 50°) and hence assembly in crystals, increases the fluorescence enhancement from ∼30 (1a ) to ∼900 (1c ). A methodology based on ab initio and lattice energy calculations and analysis of the organization of molecules and their transition dipoles in crystals is developed, to quantitatively assess the inhibition of excited state relaxation and relative energy transfer rates in solids. This approach provides insight into the contribution of intra and intermolecular pathways to the structural tuning of the emission enhancement in1a–c, and a rational basis to tailor highly emissive molecular solids.